PENINGKATKAN KEMAMPUAN MENULIS NOTASI BALOK MELALUI METODE SOLFEGIO PADA KELAS VIII-A DI SMP NEGERI 3 KEDIRI - Yayuk Siti Rahayu; Ninik Harini (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2021)
Abstract : The goal of the research is to develop the quality students’ learning result in writing partitur / musical scale through solfegio method the students of VIII A at SMPN 3 Kediri. The kind of research is class action research which is done in two cycles. Collecting data is done by using observation technique, interviewing test, and documentation. The result of this assement in cycle is 70,5% students have got the minimum standard of assessment, while in cycle 2 there are 97,1% students have achieved the minimum standard of assessment. So, it can be concluded that. The learning result of students in writing musical scale is developed shrough solfeggio method. Key words : The enhancement, The ability of writing, solfegio music.